Hubungan Antara Gaya Belajar dan Prestasi Belajar Siswa Kelas XI pada Mata Pelajaran PAI di SMAN 9 Manado - Sarini Musyafiah Ali (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2019)
This study aims to determine the relationship between student learning styles and student achievement in class XI Islamic Religious Education subjects at SMAN 9 Manado. Data collection, using a quantitative approach with 2 variables, namely variable X (Learning Style) and Y variable (Learning Achievement). This research uses non-parametric statistical data based on rank, level, or ordinal preparation. Population in this study were students of class XI who are Muslim whose number of samples is 60 people, 30 have been tested and 30 others are research samples. After testing normality of data using the chi square test, it was found that variable X X2hitung = 346,41 and Y X2hitung = 123,8. While for X 2tabel with dk=k-1= 7-1=6  obtained X 2tabel 12.592 and dk= k-1= 6-1=5 obtained X 2tabel 11.070 with an error rate of 5% turns out X2 count  X 2tabel. In conclusion, the X and Y variable data are not normally distributed. So researchers used the rho correlation test. And results are manually obtained rshitung = 0,991. Where results of rshitung is greater than rttable or 0.991 0.364 then Ha is accepted meaning that there is a significant relationship between learning styles and learning achievement.